STATINS IN THE TREATMENT AND PREVENTION OF CARDIOVASCULAR DISEASES: REPETITION OF THE PAST AND OPTIMISM FOR THE FUTURE - L. N. Malay (Рациональная фармакотерапия в кардиологии)
Statins, the most common drugs for reduction in lipid levels, are “strategic” medicinal products for the treatment and prevention of cardiovascular diseases caused by atherosclerosis. The milestones of lipid-lowering therapy history are presented as well as its contemporary aims and their implementation with focus on rosuvastatin. Data of recent metaanalysis regarding statins efficacy in primary and secondary prevention of cardiovascular complications, good safety and tolerability profile were presented. Treatment of patients with acute coronary syndrome with modern statins in high doses is discussed specially. Clinical case study of long-term treatment with rosuvastatin 20 mg/day is described. Frequency of statin prescriptions and achievements of target lipid levels in real medical practice among population of Russian patients is evaluated according to results of LIS study and PROFILE registry. Results of Russian studies of therapeutic equivalence of generic drug with original rosuvastatin are presented.